Effect of Optiglaze Coating on the Staphylococcus aurous and Porosity of Heat Cured Acrylic Material - Rashid , Amal A (Journal of Baghdad College of Dentistry, 2022)
Background: Polishing technique for acrylic resin material have great effect on properties of acrylic material and bacterial colonization such as staphylococcus aurous, which are responsible for many acrylic prosthetic infections such as the commonly ocular infections. Ineffective polishing technique could affect roughness and subsequently porosity of acrylic materials.So, a new effective method for polishing acrylic was used depending on the use of optiglaze coating material. So, this study aimed to evaluate the effect of optiglaze polishing on porosity of acrylic resin material and staphylococcus aurous activity in comparison to conventional polishing technique. Materials and methods: Specimen(n=120) were prepared :20 specimens constructed as circle shaped diameter 30mm with 1 mm thickness for porosity  test (10 control polishing by conventional technique and 10 polishing by optiglaze technique). Other 82 specimens were prepared as circle specimen (6mm diameter and 1mm thickness) for sensitivity and adherences test ( each test have 20 specimens10 control and 10 optiglaze) and 42 specimens for viability test for three dilution,21 specimens for control and 21 for optiglaze (7 specimens for each dilution). Porosity were tested by light microscopic while agar well technique, adherence test and viability count test were tested for antibacterial activity of optiglaze against staphylococcus aurous.Result: The high mean value for porosity test was recorded by control while low mean value was recorded by optiglaze group with significant differences between them. Sensitivity and adherence test high mean value recorded by optiglaze with highly significant differences in comparison to control. Viability count test all dilution 10-7 ,10-6, 10-5 showed highly significant reduction in viability count of staphylococcus aurous by optiglaze group in comparison to control. Conclusion Polishing technique by Optiglaze significantly decrease porosity of acrylic resin and this method inhibited growth of staphylococcus aurous, and decrease its viable count (have antibacterial effect) but had less effect in adherence of this bacterial in comparison to control.